Designing a training program on quality improvement and patient safety for nursing students - Hendri Hadiyanto; Lutiyah Lutiyah; Mary Ann C. Nery (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Patient safety is a fundamental component of healthcare, aimed at delivering care that is effective, efficient, and free from harm. With the increasing complexity of medical procedures and treatments, prioritizing patient safety is essential to minimize errors and adverse outcomes. Such efforts are not only vital for enhancing patient health but also for fostering public trust in healthcare services. Purpose: To design a training program focusing on quality improvement and patient safety for nursing students. Method: An exploratory sequential mixed-method design was employed, comprising three phases. The initial phase utilized a qualitative approach through semi-structured interviews with nursing students to gather in-depth insights. The second phase involved the development of an intervention program based on the qualitative findings, specifically tailored to improve quality and patient safety competencies. The third phase focused on expert validation of the developed program. Results: The qualitative analysis revealed five key themes: (1) Prioritizing Patient Safety, (2) Ensuring Accuracy in Patient Care, (3) The Importance of Infection Control, (4) Training as a Core Practice Component, and (5) The Need for Interdisciplinary Collaboration. Based on these themes, a 12-month training program was designed. Quantitative validation yielded favorable results, with an Item Content Validity Index (I-CVI) of 0.80, a Universal Agreement (UA) score of 0.80 (classified as Good), and an Average Agreement (AA) score of 0.81 (also classified as Good). Conclusion: A robust quality and patient safety framework encompasses various critical components, including the establishment of a safety culture, identification of potential risks, and the implementation of preventive strategies to reduce harm. Suggestions: Healthcare organizations, educators, and providers should adopt structured, time-bound strategies to enhance patient safety and care quality. These should include continuous training initiatives, biannual competency evaluations, and the application of quality improvement methodologies, accompanied by systematic monitoring and reporting of progress.